Perceptions of teachers' goals relationships with students' goal-orientations and learning strategies - Cabigas, Louise Marie Q. (2008)
This study sought to determine if perceived teacher-emphasis on achievement goals is related to the adoption of either a mastery or performance-oriented goal. It also investigated the learning strategies used by students with different goal orientations and if the circumstances set by the teacher are associated to the use of either an adaptive or maladaptive learning strategy. It is hinged on the Goal-Orientation Theories. 180 Grade Six pupils currently enrolled in various elementary schools in Quezon City were asked to answer a questionnaire. Results showed that when students perceived a high mastery teacher, they would pursue more adaptive learning strategies. Effort was utilized by both performance and mastery-oriented students, though more mastery-oriented students acknowledged the value of learning from mistakes.
Thesis (M.A. Educational Psychology)--University of the Philippines, Diliman.
Keywords: Teacher-student relationships -- Philippines -- Quezon City; School children -- Philippines -- Quezon City -- Attitudes; Elementary schools -- Philippines -- Quezon City; Motivation in education -- Philippines -- Quezon City; Goal (Psychology) -- Philippines -- Quezon City; Mathematics -- Study and teaching (Elementary) -- Philippines -- Quezon City